Comparison of vitamin C content in citrus fruits by titration and high performance liquid chromatography (HPLC) methods - Ramli, Fatin Najwa; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Vitamin C is one of the essential vitamins for human and animal. Many methods were developed for the determination of vitamin C such as spectrophotometry, electrophoresis, titration, and high performance liquid chromatography (HPLC). This study aims to compare vitamin C content of citrus fruits (orange, grapefruit, lemon, lime, kaffir lime and musk lime) using indophenol titration and HPLC-PDA methods. In the titration method, orange has the highest vitamin C content (58.30 mg/100g) followed by grapefruit (49.15 mg/100g), lemon (43.96 mg/100g), kaffir lime (37.24 mg/100g), lime (27.78 mg/100g) and musk lime (18.62 mg/100g). While, in the HPLC method orange also leads with the highest vitamin C content (43.61 mg/100g) followed by lemon (31.33 mg/100g), grapefruit (26.40 mg/100g), lime (22.36 mg/100g), kaffir lime (21.58 mg/100g) and musk lime (16.78 mg/100g). Orange is the best source of vitamin C while musk and kaffir lime have lower content. Significant differences were observed in vitamin C of samples by both methods. Both methods are suitable for the determination of vitamin C, however HPLC method is more accurate, precise and specific.